Superior gait performance and balance ability in Latin dancers - Liu, Yen-Ting; Lin, Ang-Chieh; Chen, Szu-Fu; Shih, Chih-Jen; Kuo, Tien-Yun; Wang, Fu-Cheng; Lee, Pei-Hsin; Lee, Adeline Peiling (Frontiers in Medicine, 2022)
Background: Latin dance consists of various fast and stability-challenging movements that require constant body adjustments to maintain proper posture and balance. Although human gaits are assumed to be symmetrical, several factors, including lower limb dominance, ground reaction forces, lower limb muscle power, foot placement angle, and range of joint motion, can contribute to asymmetrical behavior of the lower extremities in healthy adults. Gait impairment can lead to a high risk of falling, diminished mobility, and even cognition impairment. We hypothesized that Latin dancers may have a more symmetric gait pattern and better balance ability than healthy non-dancer controls. Methods: We investigated the impact of Latin dance training on gait behaviors and body balance. We recruited Latin dancers and normal healthy subjects to conduct walking experiments and one-leg stance tests, and measured their kinematic data by inertial measurement units. We then defined four performance indexes to assess gait performance and body stability to quantify the potential advantages of dance training. Results: We found that the two gait asymmetric indexes during the walking test and the two performance indexes during the one-leg stance tests were better in Latin dancers compared with the normal control group. The results confirmed the superiority of Latin dancers over the normal control group in both gait symmetry and balance stability. Our results suggest that Latin dancing training could effectively strengthen lower limb muscles as well as the core muscle groups, thereby improving coordination and enhancing gait performance and balance. Conclusion: Latin dance training can benefit gait performance and body balance. Further studies are needed to investigate the effect of Latin dance training on gait and balance outcomes in healthy subjects and patients with gait disorders.